IFPRI Malawi maize market report, October 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
On average, retail prices of maize stabilized in October at a level below their pre-election peak. National-level price stability concealed market-level variations in maize prices. Imports continued dominating cross-border trade in maize.